Travel behaviour response to major transport system disruptions: Implications for smarter resilience planning - Greg Marsden; Jillian Anable; Jeremy Shires; Iain Docherty (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2016)
The current focus of transportation policy around disruptive events is to adopt an engineering resilience-oriented approach, which focuses on returning assets to good workable order as soon as possible. This will remain critically important in the future to reduce the scale and severity of disruptive events which are likely to become more commonplace in many locations due to climate change. It is, however, only one part of ensuring that such events have more limited impacts on society and the economy. A broader consideration of societal resilience and responses outside the transport sector is needed. People travel in order to take part in activities (work, education, caring and so on), and a smarter resilience response requires us to better understand these activity patterns and intervene accordingly. There is significant adaptive capacity within society that could be better harnessed to reduce the impacts of disruptive events. The work also shows that many of our assumptions about the short and long run impacts of disruptive events need re-examining to get a fuller picture of the true economic effects of disruptive events on society and the economy. Without this it will be difficult to make the case for many types of resilience investment. This briefing paper presents evidence collected from new studies of behavioural adaptation during disruptive events and uses this to identify four areas for action to improve how we plan for resilience and how we assess the worth of different types of investment strategy: 1. The development of Smart Resilience Strategies - which are a combination of transport and non-transport responses which work together to minimize the impacts of temporary infrastructure loss; 2. Measures to improve the usefulness, impact and co-ordination of communications with the public and businesses during disruptions, enabling social adaptation and reducing time wasted in unnecessarily perilous and extended journeys; 3. A continued programme of developing the capacity of travellers and businesses to adapt to different events through greater multi-modality and an increase in smart and flexible working practices; and 4. A reassessment of the approach to understanding the economic impacts of disruptive events which extends well beyond the apparent reductions in flows and increases in journey times observed on the networks and captures the societal and economic impacts in a more holistic way.
Keywords: 330; Störungsmanagement; Verkehrsverhalten; Verkehrsökonomik; Verkehrspolitik